Construction of EFL Learning Object Materials for Senior High School - Kartika, Diah Ayu Ika; Nurkhamidah, Neni; Santosa, Imam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The realm of teaching has shifted into another paradigm in this era. Many initiatives in education bring all aspects into to–the–point and instant teaching–learning process. Other than that, English teaching–learning activity faces huge obstacles. Hence, learning object materials appeared to be the promising solution to this matter since it brings ease for both educators and learners. Learning object materials create simple and clear teaching–learning process. Thus, this study aims at describing the processes of composing Learning Object Materials and formulating the proposed Learning Object Materials based on Curriculum 2013. This study designed to focus on proposing EFL learning object materials for Senior High School of twelfth graders. A content analysis employed as the method of this study.The result showed seven stages on constructing the learning object materials. The learning object materials proposed were video, presentation, PDFs, animation, infographics, gamification, and quiz.